The association between N-methyl-d-aspartate receptor availability and glutamate levels: A multi-modal PET-MR brain imaging study in first-episode psychosis and healthy controls. (September 2022) - Beck, Katherine; Arumuham, Atheeshaan; Brugger, Stefan; McCutcheon, Robert A; Veronese, Mattia; Santangelo, Barbara; McGinnity, Colm J; Dunn, Joel; Kaar, Stephen; Singh, Nisha; Pillinger, Toby; Borgan, Faith; et al.
Background: Evidence from post-mortem studies and in vivo imaging studies suggests there may be reduced N -methyl-d -aspartate receptor (NMDAR) levels in the hippocampus in patients with schizophrenia. Other studies have reported increased glutamate in striatum in schizophrenia patients. It has been hypothesised that NMDAR hypofunction leads to the disinhibition of glutamatergic signalling; however, this has not been tested in vivo. Methods: In this study, we investigated the relationship between hippocampal NMDAR and striatal glutamate using simultaneous positron emission tomography-magnetic resonance (PET-MR) imaging. We recruited 40 volunteers to this cross-sectional study; 21 patients with schizophrenia, all in their first episode of illness, and 19 healthy controls. We measured hippocampal NMDAR availability using the PET ligand [ 18 F]GE179. This was indexed relative to whole brain as the distribution volume ratio (DVR). Striatal glutamatergic indices (glutamate and Glx) were acquired simultaneously, using combined PET-MR proton magnetic resonance spectroscopy ( 1 H-MRS). Results: A total of 33 individuals (15 healthy controls, 18 patients) were included in the analyses (mean (SD) age of controls, 27.31 (4.68) years; mean (SD) age of patients, 24.75 (4.33), 27 male and 6 female). We found an inverse relationship between hippocampal DVR and striatal glutamate levels in people with first-episode psychosis (rho = −0.74, p < 0.001) but not in healthy controls (rho = −0.22, p = 0.44). Conclusion: This study show that lower relative NMDAR availability in the hippocampus may drive increased striatal glutamate levels in patients with schizophrenia. Further work is required to determine whether these findings may yield new targets for drug development in schizophrenia.